Aplicación del sistema lean manufacturing en el proceso de producción de bloques de balsa de la Empresa Produsiembal Cía. Ltda. - Semes Suárez, María Justina (2019)
This research project was carried out in the company Produsiembal Cía. Ltda., in order to obtain a process of continuous improvement in the production area applying the Lean manufacturing methodology, using the 5S and Kaizen tools that are focused on quality control. Evaluating 3 of the main areas of the company: reception, machining and gluing; Because they are conformed by the majority of the number of the personnel, therefore there is greater movement and risks of accidents or failures in the production process. The goal of applying Lean manufacturing tools is to promote a culture of cleanliness and organization that leads to better results by implementing a continuous improvement plan, where the aim is to reduce waste or wastage due to fluctuation of suppliers that cause scarcity in the raw material and therefore failures of production, besides using tools, equipment or spaces unnecessary or inadequate for the efficient elaboration of his work tasks. To address the topic of this work identified possible problems through observation, interviews and surveys to collaborators, in addition to using the distribution charts of areas, process diagrams, flow and process route Productive to know the current situation of the company. In addition, the theoretical and conceptual foundation that facilitates the application of the system of continuous improvement; It will make it easier to carry out the results and discussion of the research that will serve to determine the conclusions and recommendations obtained through the investigation. The same that facilitate the elaboration of a plan of continuous improvement. Key words: Lean manufacturing, process, continuous improvement, culture, quality control.